La lúdica: una estrategia didáctica para la disminución de conductas disruptivas y la promoción de la convivencia escolar. (2018)
The present research project shows the design of a play-based didactic strategy for the reduction of disruptive behaviors and the promotion of school coexistence in the students of grades 4 and 5 of primary school of the Timba Educational Institution, located in the municipality of Buenos Aires, department of Cauca. The sample consisted of 9 teachers and 80 students from the fourth and fifth grades. From the surveys a faculty and teachers have been made about the most frequent disruptive behaviors in the classroom and the state of school coexistence, a booklet with the activities that allowed to diminish this phenomenon and promote school coexistence was designed. The results, that in the institution, the relationship between teachers and students, school coexistence is good, however, physical activities in the classroom, nicknames and colleagues' offices are frequent, forcing other classmates to do Things that do not want, threaten, insult and exclude from some friends' groups. Finally, the proposal was validated through the experts' criteria.